Positively selected modifications in the pore of TbAQP2 allow pentamidine to enter Trypanosoma brucei - Alghamdi, Ali H; Munday, Jane C; Campagnaro, Gustavo Daniel; Gurvic, Dominik; Svensson, Fredrik; Okpara, Chinyere E; Kumar, Arvind; Quintana, Juan; Martin Abril, Maria Esther; Milić, Patrik; Watson, Laura; Paape, Daniel; et al. (eLife, 2020)
Mutations in the Trypanosoma brucei aquaporin AQP2 are associated with resistance to pentamidine and melarsoprol. We show that TbAQP2 but not TbAQP3 was positively selected for increased pore size from a common ancestor aquaporin. We demonstrate that TbAQP2's unique architecture permits pentamidine permeation through its central pore and show how specific mutations in highly conserved motifs affect drug permeation. Introduction of key TbAQP2 amino acids into TbAQP3 renders the latter permeable to pentamidine. Molecular dynamics demonstrates that permeation by dicationic pentamidine is energetically favourable in TbAQP2, driven by the membrane potential, although aquaporins are normally strictly impermeable for ionic species. We also identify the structural determinants that make pentamidine a permeant although most other diamidine drugs are excluded. Our results have wide-ranging implications for optimising antitrypanosomal drugs and averting cross-resistance. Moreover, these new insights in aquaporin permeation may allow the pharmacological exploitation of other members of this ubiquitous gene family.
Keywords: aquaporin; pentamidin; Drug Resistance; drug transport; mutace; Trypanocidal Agents; trypanocidální látky; pentamidine; chemical biology; infectious disease; Aquaporin 2; Melarsoprol; Aquaporins; léková rezistence; Trypanosoma brucei brucei; Trypanosoma brucei; biochemistry; Animals; Trypanosomiasis, African; zvířata; akvaporiny; trypanozomóza africká; melarsoprol; drug resistance; Mutation; Pentamidine; akvaporin 2; microbiology